AB0844 Detection of low Levels of Vitamin D or Free Testosterone in Patients Receiving Prednisone for A Rheumatic Disease. (10th June 2014) - Imran, M.; Singh, H.; Lukert, B.; Lindsley, H.
Abstract : Objectives: The purpose of this cross-sectional study was to determine the prevalence of vitamin D insufficiency in males and females and testosterone deficiency in males, who have an increased risk for osteoporosis due to prednisone therapy. Mild to moderate vitamin D insufficiency causes osteoporosis. Twenty five-hydroxy vitamin D <32 ng/ml leads to reduce calcium absorption, higher concentration of parathyroid hormone, and increased bone resorption 1 . Methods: Blood samples were obtained from rheumatology practices, (four community-based and one university-based) from men and women with a rheumatic disease. The patients were >40 years old and were taking at least 5 mg of prednisone for at least the past 30 days. Serum levels of 25-hydroxy vitamin D (25-OHD), free testosterone in males (FT-M) only, and osteocalcin (OC) were measured in 44 individuals. Non –parametric analysis of the data was done as shown in Table 1 . Results: Twenty nine patients (65%) were found to have 25-OHD levels <32; of these only 41% were on over the counter (OTC) vitamin D as opposed to 80% with 25-OHD >32. Fourteen males (58%) had testosterone deficiency (<1 ng/dl). Increasing prednisone dose correlated with lower mean OC values (P=0.003). Conclusions: Our sample revealed a high prevalence of vitamin D insufficiency and underutilization of OTC vitamin D in rheumatology practices. There was an encouraging trend towards higher vitamin D levels with use of OTC vitamin D. A large number of male patients were noted to have low testosterone levels. In patients with a rheumatic disease on prednisone therapy, there appears to be a high incidence of vitamin D insufficiency and testosterone (in males) deficiency. Routine screening for 25-OHD and free testosterone (in males) should be utilized to reduce the risk of osteoporosis. References: Luckeyet al. J ClinEndocMetab 2003 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2623